Advancements in semi-solid metal processing of ADC12 aluminium alloy: Microstructure and mechanical properties - Sujeet Kumar Gautam; Bipin Kumar Singh; Ritesh Kumar Singh; Sanjiv Kumar Tiwari; Rajat Upadhyaya; Himanshu Khandelwal; Gaurav Kumar; S M Mozammil Hasnain; Rustem Zairov (Results in Engineering)
Semi-solid metal processing is a well-established manufacturing method that allows for the efficient production of components with excellent mechanical properties and consistent, defect-free microstructures, all at a lower cost than traditional techniques. This review examines explicitly the ADC12 die-cast aluminium alloy, which has received limited attention in research compared to more extensively studied alloys such as A356, A357, and Al-6061. It consolidates findings related to the semi-solid metal processing of the ADC12 alloy, addressing system evolution, microstructure enhancement, and the relationship between microstructure and mechanical properties. The results revealed that SSM had higher mechanical properties with UTS, ductility, and hardness as 223 MPa, 6.5 %, and 87 HV, respectively, compared to conventional processing routes with UTS, ductility, and hardness as 173 MPa, 3.17 %, and 72 HV, respectively, due to higher sphericity and grain refinement (0.87 and 42 µm). The review also emphasizes the physical mechanisms influencing alloy behavior, identifies existing research gaps, suggests potential solutions, and explores the future prospects of semi-solid metal processing in improving the performance and reliability of ADC12 alloy across various industrial applications.